2012
DOI: 10.1089/aid.2011.0263
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of HIV Replication by Multiple Modulators and Their Implication for a Novel Antiviral Therapy

Abstract: Transcriptional regulation is critical for the human immunodeficiency virus 1 (HIV-1) life cycle and is the only step at which the virus amplifies the content of its genetic information. Numerous known and still unknown transcriptional factors, both host and viral, regulate HIV-1 gene expression and latency. This article is a comprehensive review of transcription factors involved in HIV-1 gene expression and presents the significant implications of nuclear factor kappa B (NF-κB) and the HIV-1 transactivator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 178 publications
(180 reference statements)
0
22
0
Order By: Relevance
“…It might also be of interest to understand the molecular determinants modulating SAMHD1 expression. In particular, as some transcriptional factors are important for HIV-1 replication [36,37], the study of their relation with SAMHD1 expression may be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…It might also be of interest to understand the molecular determinants modulating SAMHD1 expression. In particular, as some transcriptional factors are important for HIV-1 replication [36,37], the study of their relation with SAMHD1 expression may be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Provirus refers to the viral form that has been integrated into the cell's genome and is inherited through each cell division. Latent means it is transcriptionally inactive, but is able to re-activate after stimulation [16][17][18][19] and is capable of causing substantial viremia when therapy ceases [20,21] . The viral reservoir, a term used to refer to the latently infected cells as a whole, is maintained throughout the life span of an infected individual.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of HIV latency is a multifactorial event involving several factors, including (i) the chromatin environment at the site of integration, (ii) transcriptional interference, (iii) a lack of host transcription factors needed for viral gene expression, (iv) the presence of host transcriptional repressors, and (v) epigenetic silencing of viral transcription (32)(33)(34)(35)(36). The elucidation of molecular mechanisms by which HIV type 1 (HIV-1) persists within infected cells provides a basis for a new therapeutic approach aimed toward combining HIV gene expression therapy and an ARV regimen.…”
Section: Hiv Latency As a Critical Obstacle To The Eradication Of Hivmentioning
confidence: 99%
“…This is carried out by producing an environment permissive for transcription by altering the degree of acetylation and methylation of histones and nonhistone molecules. HDACi compounds such as trichostatin A, trapoxin, valproic acid, sodium butyrate, or vorinostat (VOR; also known as suberoylanilide hydroxamic acid [SAHA]) have the ability to disrupt latent HIV infection in both cell culture models and ex vivo assays using cells from HIV-1-infected patients or latently infected cell lines (36,(79)(80)(81)(82)(83)(84)(85). Archin et al (83) demonstrated that a single dose of VOR increased biomarkers of cellular acetylation and simultaneously increased HIV RNA expression in resting CD4 ϩ cells from HIV-1-infected patients.…”
Section: Potential Therapeutic Interventions Aimed To Decrease Hiv Rementioning
confidence: 99%